Primary percutaneous coronary intervention for cardio-cerebral infarction: a case report - Watanabe, Tomomi; Kobara, Satoshi; Amisaki, Ryosuke; Yamamoto, Kazuhiro (Frontiers in Cardiovascular Medicine, 2023)
Background: Acute myocardial infarction (AMI) and acute ischemic stroke (AIS) are the leading causes of death globally. Cardio-cerebral infarction (CCI) is the rare occurrence of AMI and AIS, either at the same time or one after the other. Treatment recommendations are not clear in case of occurrence of AMI and AIS simultaneously, especially strategy of primary percutaneous coronary intervention (PCI).Case presentation: We report consecutive 7 case series of patients with CCI who underwent primary PCI in our institute. Comorbidities, strategy of primary PCI, and outcomes were investigated. All patients presented with the chief complaints associated with stroke. Atrial fibrillation was complicated in 5 of 7 CCI patients, and 4 of 5 AF patients were not anticoagulated. The major causes of stroke were cardiogenic and/or hemodynamic in this case series. All patients showed total occlusion in the culprit lesion and 6 patients had other diseased vessels. Thrombus aspiration was mainly chosen as reperfusion strategy in PCI. However, only 2 patients were diagnosed as definitive coronary embolism, and stenting was needed in 6 patients due to severe atherosclerotic lesion in culprit coronary artery. Final TIMI 3 flow was achieved only in 4 patients. Hemorrhagic complications occurred in 3 patients. Two patients passed away in hospital stay and most had to be transferred for rehabilitation.Conclusions: CCI was a rare but fatal condition in patients who underwent primary PCI. Although CCI was associated with concomitant atrial fibrillation, organic coronary stenosis which requiring stenting for revascularization was present in almost cases. Given the complexity of coronary artery lesions and high in-hospital mortality, further investigations are needed to determine the optimal treatment strategy.